PKM Socialization and Training on Financial Reports and Optimizing Digitization of the Economy in Development UKM/UMKM House of Friends of Mother, Medan Helvetia Village - Nasution, Abdillah Arif; Yuliati, Tetty; Risanty; Agustrisna, Juwita; Bilqis R, May Hana (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Rumah Kawan Bunda is a forum for empowering women in entrepreneurship. Rumah Kawan Bunda has various educational and collaboration programs to increase the production and sales of its members. The purpose of Rumah Kawan Bunda itself is as a space for women entrepreneurs who want to improve their entrepreneurial competence as well as a place for education and business collaboration between fellow entrepreneurs. It can be said that Rumah Kawan Bunda is the answer for women entrepreneurs who want to advance their business and increase their competence in selling both online and offline in this digital era. To continue to support the development of MSME players so that they can be competitive and contribute to the national economy, it is necessary to take steps to motivate and support MSMEs by providing guidance and assistance so that they can be more focused. Therefore, we will conduct socialization and assistance to MSMEs in preparing financial reports so that they can be used as decision-making tools in calculating business profits, and can increase access to capital to get investors. In addition, to overcome the problems of MSMEs, namely access to market products in the face of free trade and the 4.0 revolution, Micro, Small and Medium Enterprises (MSMEs) can take advantage of electronic commerce or E-commerce as a means of marketing their products.